The Optimation of Fermentation Time, Antibacterial Activity and Profiling Secondary Metabolite of Symbiont Fungi from Sponge Gelliodes fibulata - Siska Rusmalina; Mahfur; Nunung Hasanah; Mochamad Ardy Wiyono; Nonik Nur Ekayanti; Jacinda Caroline Nathania (Universitas Ahmad Dahlan, 2024)
Symbiont fungi are organisms that live in sponges tissue. Sponges are known to contain many metabolites which have the potential to be used as raw materials for medicine. Sponge Gelliodes fibulata belongs to the category demospongiae. The purpose of this study was to determine the optimal time to obtain the best secondary metabolite profile results in the sponge symbiont fungus Gelliodes fibulata. This research is included in experimental research. Beginning with the fungi culture of the sponge Gelliodes fibulata. Time variations 2, 4, 6, 8, 10, 12, and 14 are used to see differences in secondary metabolite production. A liquid extraction process is carried out to obtain secondary metabolites produced during fermentation. The final stage is to carry out qualitative analysis with TLC and antibacterial testing with the well-diffusion method. The results obtained indicate that the length of fermentation time influences the secondary metabolites obtained and automatically influences their antibacterial activity. The profile of secondary metabolites from TLC showed that the 10th day of fermentation had the secondary metabolites with high complexity and the highest yield 0.086%. The results of antibacterial activity showed that the 10th day of fermentation had the largest inhibition zone with 7.75 ± 0.44 mm compared to the other days of fermentation